2014
DOI: 10.1097/rct.0b013e3182a58a8c
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Coronary Artery Bypass Graft Patency

Abstract: In conclusion, MDCT can be used noninvasively with a lower radiation dose for the assessment of restenosis in CABG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Overall, CCT has a high sensitivity, specificity and NPV compared with ICA and should be recognized as an accurate and noninvasive method for evaluation of graft patency in symptomatic CABG patients. Furthermore, the continuous technological improvement of CT scanners enables the assessment of challenging patients, such as those with high heart rate, 75 while reducing radiation exposure and contrast media volume 76–79 . Finally, the prognostic utility of CCT in CABG patients has been demonstrated 80–82 : patients with two or more unprotected coronary territories are at higher risk for cardiac events.…”
Section: Cardiac Computed Tomography For Coronary Artery Bypass Graft...mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, CCT has a high sensitivity, specificity and NPV compared with ICA and should be recognized as an accurate and noninvasive method for evaluation of graft patency in symptomatic CABG patients. Furthermore, the continuous technological improvement of CT scanners enables the assessment of challenging patients, such as those with high heart rate, 75 while reducing radiation exposure and contrast media volume 76–79 . Finally, the prognostic utility of CCT in CABG patients has been demonstrated 80–82 : patients with two or more unprotected coronary territories are at higher risk for cardiac events.…”
Section: Cardiac Computed Tomography For Coronary Artery Bypass Graft...mentioning
confidence: 99%
“…67,68 Using a whole organ high-definition CT scanner Andreini et al 69 showed that coronary CCT can evaluate ISR with high diagnostic accuracy and, moreover, the use of CCT stress perfusion 70 75 while reducing radiation exposure and contrast media volume. [76][77][78][79] Finally, the prognostic utility of CCT in CABG patients has been demonstrated [80][81][82] : patients with two or more unprotected coronary territories are at higher risk for cardiac events.…”
Section: Cardiac Computed Tomography For Stent Patency Evaluationmentioning
confidence: 99%
“…Dual-source CT technology became available in 2005 and has provided high temporal resolution for coronary CT angiography (CTA) [ 8 ]. High-pitch value and table speed have made it possible to obtain all volumetric data of the heart with radiation exposure as low as 1 mSv in a single cardiac cycle [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%